Electrochemical study of heavy metals and metallothionein in yeast Yarrowia lipolytica - Strouhal, Martin; Kizek, René; Vacek, Jan; Trnková, Libuse; Nemec, Miroslav (Bioelectrochemistry (Amsterdam, Netherlands), 2003)
The bioaccumulation of heavy metals (cadmium, nickel, cobalt and zinc) and the effect of these metals on the production of metallothionein and metallothionein-like proteins (MT) in Yarrowia lipolytica was studied by electrochemical methods. The concentrations of heavy metals were determined by differential pulse voltammetry (DPV). A combination of the constant current chronopotentiometric stripping analysis (CPSA) and adsorptive transfer stripping technique (AdTS) was used to determine the content of MT in cells. Both the bioaccumulation of heavy metals and the production of MT in different cell compartments of Y. lipolytica exposed to heavy metals were monitored. The LD(50) of each metal was determined from the number of viable cells in yeast cultures: LD(50)Cd (37.5 microM), LD(50)Ni (570 microM), LD(50)Co (700 microM), and LD(50)Zn (1800 microM). The highest concentrations of heavy metals were found in the cell wall and membrane debris while the lowest concentrations were detected in the cytoplasm. Cadmium and nickel showed the most significant effect on the production of MT. This study provides new insights into the ecophysiology of microorganisms and demonstrates the potential use of these electrochemical methods in biotechnology.
Keywords: Metallothionein; těžké kovy; metalothionein; Culture Media, Conditioned; Electrochemistry; buněčné dělení; kultivační média speciální; Time Factors; Cell Membrane; Animals; buněčná stěna; cytoplazma; elektrochemie; Cell Division; Cell Wall; Cytoplasm; zvířata; buněčná membrána; časové faktory; Yarrowia; Metals, Heavy